2016
DOI: 10.1590/0100-3984.2014.0111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of power Doppler and thermography for the selection of thyroid nodules in which fine-needle aspiration biopsy is indicated

Abstract: ObjectiveTo compare two methods-power Doppler and thermography-for the analysis of nodule vascularization and subsequent selection of nodules to be biopsied.Materials and MethodsA total of 510 subjects with thyroid nodules were analyzed by power Doppler and submitted to fine-needle aspiration biopsy (FNAB). Thirty-seven patients were submitted to nodule excision (29 due to carcinoma or suspected carcinoma and 8 by patient choice). Among those patients, power Doppler had raised the suspicion of malignancy in 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…They concluded that thermography is more precise than power doppler for the indication of FNAB of thyroid nodules suspected of malignancy. 20 The combination of several suspicious US features is definitely more accurate than that of any single characteristic in predicting thyroid nodule as malignant. In 2009, Horvath et al and Park et al established a thyroid imaging reporting and data system (TI-RADS) to stratify cancer risk in thyroid nodules based on 10 and 12 sonographic features respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that thermography is more precise than power doppler for the indication of FNAB of thyroid nodules suspected of malignancy. 20 The combination of several suspicious US features is definitely more accurate than that of any single characteristic in predicting thyroid nodule as malignant. In 2009, Horvath et al and Park et al established a thyroid imaging reporting and data system (TI-RADS) to stratify cancer risk in thyroid nodules based on 10 and 12 sonographic features respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this problem, Infrared Thermography has emerged as a low-cost and noninvasive method for investigating TN 6,7 . However, few studies have seriously evaluated this approach specially going up to the use of new Artificial Intelligence techniques, as the convolutional neural networks (CNNs), to promote a final conclusion on this subject as the here presented one 8 .…”
Section: P Damião 1* J R G Montero M B H Moran 2 R Amentioning
confidence: 99%
“…Some of them only analyze the thermal effects of hyperthyroidism and hypothyroidism by IRT [20,21]. There are works on theoretical studies of the possibility of uses IRT in thyroid nodule diagnosis [18,[22][23][24][25][26], as well as paper evaluating the uses of IRT as complementary technique to help on the indication of biopsy of nodules suspected of malignancy [27]. However, there is no work on simulating a complete protocol of thermography specially including the transient phase: this aspect has been considered crucial on investigation the possibility of IRT for cancer diagnosis in previous work [28] and is accomplished in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and biologically, the similarity or the differences of the nodules is evaluated by parameters completely diverse from those used in mechanical heat transfer analysis. Even the size, that is the most similar of all, has different ways of being measured: the length of the nodules in each direction, for instance, is measured by ultrasound exams [27] most of the time only by nodular higher and smaller diameters, without relation with the body axial planes or any fixed axial reference of the numerical model. Furthermore, thyroid nodules can be at different positions and depths inside the gland regardless of their diagnosis [27, 34].…”
Section: Introductionmentioning
confidence: 99%